PENINGKATAN MINAT ANAK USIA DINI MELALUI PEMBELAJARAN AKTIF TK MUARA KASIH KUANTAN SINGINGI - Rusni (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2017)
This study aims to determine learning activities in increasing children's interest in drama centers at Muara Kasih Kindergarten, Pucuk Rantau District, Kuantan Singingi Regency. The method used in this research is Classroom Action Research with a total of 20 research subjects consisting of 11 boys and 9 girls. Data collection techniques data collection in this study is observation and documentation. The data analysis technique used in this research is the percentage technique. The results showed that through active learning activities, the teacher's activities in cycle II showed an increase with a percentage score of 89.6% with good criteria. Increasing teacher activity can increase children's activity in Muara Kasih Kindergarten, Pucuk Rantau District, Kuantan Singingi Regency, in cycle II with an average score of 68 or 85% with good criteria. The increase in student activity was followed by an increase in interest in children in Muara Kasih Kindergarten, Pucuk Rantau District, Kuantan Singingi Regency, an increase in interest in children in Muara Kasih Kindergarten, Pucuk Rantau District, Kuantan Singingi Regency in cycle II with an average score of 65.2 or 81.5 % with very well developed criteria (BSB).